Inflation targeting in practice : strategic and operational issues and application to emerging market economies - Blejer, Mario I....[et al] (IMF WashingtonUS, 2000)
Discusses the reasons why inflation targeting is useful, in the context of an analysis of the importance and implications of pursuing the price stability objective. Examines the details of implementation of inflation targeting in five industrial countries. Deals with emerging economies and the ways in which inflation targeting has been adapted to their circumstances.